Carbohydrate Ingestion During Prolonged Exercise and Net Skeletal Muscle Glycogen Utilization: A Meta-Analysis - Rothschild, Jeffrey A; Dudley-Rode, Harrison; Carpenter, Harriet; Smith, Abbie; Plews, Daniel J; Maunder, Ed (American Physiological Society, 2025)
Background: While some studies report attenuated net muscle glycogenolysis with carbohydrate ingestion, others show no effect, possibly due to small sample sizes or methodological differences. Objective: To determine whether carbohydrate ingestion during endurance exercise reduces net skeletal muscle glycogen use, and to identify potential moderating factors. Methods: A meta-analysis was conducted using data from 31 studies which included 48 unique effect sizes derived from crossover trials comparing carbohydrate vs. placebo ingestion during prolonged endurance exercise. Standardized mean differences (SMDs) in net muscle glycogen utilization were calculated. A multilevel random-effects model accounted for repeated estimates within studies. Subgroup and meta-regression analyses tested potential moderators. Sensitivity analyses were conducted using a range of plausible pre/post correlation values. Results: Carbohydrate ingestion was associated with a small but statistically significant muscle glycogen-sparing effect (SMD = –0.16, 95% CI: –0.30 to –0.02, p = 0.021). Subgroup and moderator analyses revealed no significant effects of exercise mode, carbohydrate type, ingestion rate, or pre-exercise glycogen on the observed effect. Translating the standardized effect into absolute units, carbohydrate ingestion was estimated to spare ~24 mmol kg-1 dry weight (95% CI: 4 to 45 mmol kg -1) of muscle glycogen, relative to placebo, during ~100 min of exercise. Conclusion: Carbohydrate ingestion during endurance exercise leads to a small but statistically significant reduction in net skeletal muscle glycogen utilization. Although no consistent moderating variables were identified, the direction of effect was consistent across studies, and the absolute magnitude of sparing may be physiologically meaningful during prolonged or repeated efforts.
Keywords: exercise; glycogenolysis; metabolism; nutrition; skeletal muscle; 42 Health Sciences; 4207 Sports Science and Exercise; Prevention; Physical Activity; Behavioral and Social Science; Clinical Research; Clinical Trials and Supportive Activities; 06 Biological Sciences; 11 Medical and Health Sciences; Physiology; 31 Biological sciences; 32 Biomedical and clinical sciences; 42 Health sciences; Humans; Muscle, Skeletal; Glycogen; Dietary Carbohydrates; Exercise; Physical Endurance; Muscle, Skeletal; Humans; Glycogen; Dietary Carbohydrates; Exercise; Physical Endurance; Humans; Muscle, Skeletal; Glycogen; Dietary Carbohydrates; Exercise; Physical Endurance